2014
DOI: 10.3934/publichealth.2014.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities with Empowering Baby Boomers for Personal Health Information Management Using Consumer Health Information Technologies: an Ecological Perspective

Abstract: “Baby Boomers” (adults born between the years of 1946 and 1964) make up the largest segment of the population in many countries, including the United States (about 78 million Americans) [1]. As Baby Boomers reach retirement age and beyond, many will have increasing medical needs and thus demand more health care resources that will challenge the healthcare system. Baby Boomers will likely accelerate the movement toward patient self-management and prevention efforts. Consumer Health Information Technologies (CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…To improve the self‐management of chronic diseases within the baby boomer population, nurses must recognise that health literacy will be influenced by multiple, and sometimes conflicting, sources of information. To cope with complicated and sometimes conflicting information, people in the baby boomer generation prefer a relationship with a trusted health care professional (LeRouge et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the self‐management of chronic diseases within the baby boomer population, nurses must recognise that health literacy will be influenced by multiple, and sometimes conflicting, sources of information. To cope with complicated and sometimes conflicting information, people in the baby boomer generation prefer a relationship with a trusted health care professional (LeRouge et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the stigma of low health literacy is significant. Patients may hide their poor health literacy (Chan, 2014;LeRouge et al, 2014;Matthews et al, 2012), which makes efficient identification of patients who need further support more difficult for clinical nurses. When working with the baby boomer generation, nurses could use socioeconomic indicators of health to screen for those people who may require further health education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with some highly historical and social events, such as World War II, the great depression, the Vietnam War, and the Fall of Berlin Wall, the appearance of the "digital age" marks a significant difference among those individuals that belong to the Z (age <24 years) and Y Generations (aged 2438 years) in comparison to those older, such as Generation X (aged 3953 years), Baby boomers (aged 5472 years), and the silent generation (aged 73-94 years) [14]. For instance, although many studies have shown that older generations are increasingly using ICTs, they continue to perceive technological advances such as the digitalization of medical records as surprising or futuristic, whereas in younger individuals it is already an expectation [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…This group is likely to have different information-seeking patterns and health awareness compared to the baby boomers who are our main patient population with pelvic floor disorders at present. On the other hand, the baby boomers are considered to be more proactive regarding their experience with pelvic floor disorders than the preceding generation of women as they were more conscious of youth, beauty and general appearance and wished to postpone aging [8]. As longevity increases, younger women will seek care for pelvic floor disorders, request more information about management options and discuss the available therapeutic interventions and will live long enough to experience treatment recurrences.…”
mentioning
confidence: 99%